Market Corrections: Jonathan Franzen and the "Novel of Globalization." - Annesley, James (Journal of Modern Literature)
This essay discusses the social and economic context presented in the book "The Corrections" by Jonathan Franzen. It emphasizes that the novel's title was provoked by the shift of the economic situation at the end of 20th century affected by market corrections in the U.S. It also describes Franzen's commitment to write social novels and cultural authority. Commentators Arjun Appadurai and Roland Robertson have also describe Franzen's works as forms of culture that have become focus to literature.